Sistem Pendukung Keputusan Penerimaan Anak Asuh Baru di Panti Asuhan Al-Washliyah Pulo Brayan Menggunakan Metode Multi-Attribute Utility Theory (Maut) - Widya Adelina; Fhery Fhery (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the development of a Decision Support System (DSS) to assist the process of accepting new foster children at the Al-Washliyah Pulo Brayan Orphanage. The previous foster child selection process was conducted manually and subjectively, making it vulnerable to unfairness and assessment errors. This study applies the Multi-Attribute Utility Theory (MAUT) method to objectively assess foster children based on eight criteria: age, family circumstances, prospective economic conditions, health, education, legal status, independence, and behavioral and social well-being. This study uses a web-based software engineering approach with the PHP programming language and a MySQL database. The results show that the application of the MAUT method can accelerate the decision-making process, improve fairness in selection, and minimize subjective bias from decision-makers. The developed system is expected to serve as a reference for other orphanages in developing more efficient and transparent digital-based admission systems.